(untitled) (Docentes 2.0 Journal, 2020)
This research aimed to analyze the application of the Cognitive Theory of Jerome Bruner as a mechanism to strengthen environmental behavior in students in the second grade of the Chuniza Educational Institution. For this purpose, a bibliographic review was carried out on the relevant aspects of the theory, as well as the work at international, national and regional levels, which were very useful for methodological design, strategy approach and analysis of the results. The type of research was qualitative with the Research-Action method, which started from a diagnostic stage where it was possible to establish that the students mentioned required strengthening their environmental behavior, since their lack of knowledge of concepts, the impact of man on nature and nature. final disposal of solid waste, among others, became evident. Based on the above, a didactic strategy was designed using playful, musical, theatrical and poetic elements; aspects that ultimately proved very effective, as dynamism was evident in the development of each activity, inferential and critical analysis of each particular environmental situation and deep reflection on the causes and consequences of the current environmental phenomenon, as well as the creation of commitments that in the end, they will serve as an example for the treatment given to such a thematic peak.